Legal Aspects in the Development of Tourism Villages in Wonogiri Regency Based on Local Wisdom - Martitah, Martitah; Sumarto, Slamet; Yudhanti, Ristina; Prabowo, Muhammad Shidqon (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2022)
Tourism development in rural areas often encounters various legal challenges, especially concerning adherence to local regulations and respect for traditional values. This paper explores the legal aspects involved in the development of tourism villages within Wonogiri Regency, focusing on the integration of local wisdom. Wonogiri, a regency in Central Java, Indonesia, boasts a rich cultural heritage and a strong tradition of community-based governance. Through a comprehensive review of existing literature and legal documents, this study examines the legal framework governing tourism village development in Wonogiri, highlighting the incorporation of local wisdom into relevant regulations and policies. Additionally, it analyzes the role of legal mechanisms in safeguarding indigenous knowledge, protecting cultural heritage, and ensuring equitable benefits for local communities. By evaluating case studies and empirical data, this research identifies best practices and challenges in aligning legal frameworks with local values, offering insights for policymakers, practitioners, and stakeholders involved in sustainable tourism development. Ultimately, this study underscores the importance of harmonizing legal norms with indigenous principles to promote responsible tourism that respects the cultural integrity and socio-economic well-being of rural communities in Wonogiri Regency and beyond.